From Traditional Agricultural Practices to Monoculture Plantations: Impacts on Indigenous Communities' Land Tenure,Land Use, and Livelihoods - Pandelaki, Tirza; Sunito, Melani Abdulkadir; Kolopaking, Lala M (Sodality: Jurnal Sosiologi Pedesaan, 2025)
The shift from traditional agriculture to monoculture plantations has significantly altered land tenure, land use, and livelihoods among the Dayak Hibun Community in villages of West Kalimantan. This study aims to examine the impacts of oil palm development on land relations, cultural values, and livelihoods within Indigenous communities embedded in the palm oil commodity supply chain.  This study uses a mixed-methods approach, combining qualitative methods such as field observations, transect, interviews, and FGDs. Snowball sampling was employed to identify key informants with deep contextual knowledge. A survey of 31 Dayak Hibun households provided quantitative data on livelihood activities, land access, and resource relations, which  strengthened the qualitative analysis. The unit of analysis was the household of Dayak Hibun farmers in Gunam Village located in the lowland area of Sanggau district. Findings indicate that households that own less than 2 hectares of oil palm farms predominantly experience survival conditions, some of which engage in consolidation intensification, and diversification. In contrast, households that own more than 2 hectares of land tend to pursue consolidation diversification, intensification, extensification, and accumulation. Cultural values serve as a collective strength across all social strata particularly for survival household condition with landholdings of less than two hectares.